P09.10 The potential impact of vaccination on the prevalence of gonorrhoea. (13th September 2015) - Seib, KL; Craig, AP; Gray, RT; Edwards, JL; Apicella, MA; Jennings, MP; Wilson, DP
Abstract : Introduction: Gonorrhoea, one of the most common sexually transmitted infections worldwide, can lead to serious sequelae, including infertility and increased HIV transmission. Recently, untreatable, multidrug-resistant Neisseria gonorrhoeae strains have been reported. In the absence of new antibiotics, and given the speed with which resistance has emerged to all previously used antibiotics, development of a vaccine would be the ideal solution to this public health emergency. Understanding the desired characteristics, target population, and expected impact of an anti-gonococcal vaccine is essential to facilitate vaccine design, assessment, and implementation. The modelling presented herein aims to fill these conceptual gaps and inform future gonococcal vaccine development. Methods: Using an individual-based, epidemiological simulation model, gonococcal prevalence was simulated in a heterosexual population of 100, 000 individuals (with a 1.7% prevalence rate) after the introduction of vaccines with varied efficacy (10–100%) and duration of protection (2.5–20 years). Results: Model simulations predicted that gonococcal prevalence could be reduced by; at least, 90% after 20 years, if all 13-year-olds were given a vaccine with 50% efficacy that does not wane. A comparable reduction in prevalence could be achieved by a vaccine with 100% efficacy that wanes after 7.5 years. A 40% reduction in prevalence would be achieved with a non-waning vaccine of just 20% efficacy. Conclusion: A vaccine of moderate efficacy and duration could have a substantive impact on gonococcal prevalence and disease sequelae, if coverage is high and protection lasts over the highest risk period (i.e. most sexual partner change) among youths. Disclosure of interest statement: This work was funded by the Australian National Health and Medical Research Council, The Australian Government Department of Health, and the National Institutes of Health USA. No pharmaceutical grants were received in the development of this study.